Utlize microalgae in order to lowering green house emission by using carbon capture - Wongsodiharjo, Deniela; Ismail Masjud, Yunita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The greenhouse effect cause the temperature in earth, one of the main contributor in GHG g emission is carbon dioxide (CO2). In order to reducing GHGs empathize in mitigation can be one of the way. By implementing Carbon capture using Algae, where it considered as the main resource of renewable biofuel in the future and possibly play important role in the mitigation of the greenhouse effect. By utilize the photosynthesis process from algae, it can be used for CO2 sequestration as a great potential to reduce GHS gas. The objectives of this research is to understanding and know the process and benefit on using microalgae as the carbon dioxide capture to mitigate climate change (reducing Green House Gas emission). Method and results: The method use in this literature review, method that firstly discussed is the general description with pro cons of carbon capture technology method also with the background in order to reducing the highest contributor of Green House gas Emission (GHGs) which is Carbon Dioxide (CO2), from this utilizing the natural process method from photosynthesis of microalgae whose need a lot source of CO2 being the most beneficial method, and the end of product create a biomass and that will be helping to reducing the use of fossil fuel. Discussing the photosynthesis system it can be far from light dependent and light independent reaction since both of it is a recycled system. Therefore, implementing carbon dioxide capture using microalgae is very useful. Though there still need improvement in this sector. Conclusion: Carbon capture using Microalgae CO2 sequestration is one of the promising way to mitigate climate change and control environmental pollution is by fixing CO2 in the atmosphere and recovering organics from wastewater.